Invasive fungal infections in solid organ transplant recipients. (September 2014) - Gavaldà, J.; Meije, Y.; Fortún, J.; Roilides, E.; Saliba, F.; Lortholary, O.; Muñoz, P.; Grossi, P.; Cuenca‐Estrella, M.; ,
Abstract: Solid organ transplant (SOT) recipients have a significant risk of invasive fungal diseases (IFD) caused mainly by Candida spp. and Aspergillus spp. Candida spp. is the most frequent agent of IFD in the transplant recipient. The absence of clinical trials and the epidemiological differences in IFD in different transplant programmes mean that there are no definitive recommendations for the diagnosis, treatment and prevention of IFD in SOT, so most of the evidence must be based on clinical experience.